Broken pin in root canal - Karanveer Singh Saluja; Babita Karda (Wolters Kluwer Medknow Publications, 2015)
Trauma may lead to fractured teeth with exposed canals in growing children. Some people have a habit of placing foreign objects to remove food plugs from the teeth. These foreign objects may act as a potential source of infection and may later lead to a painful condition. The presence of foreign object in the root canal is one of the challenging occurrences in endodontic therapy. The chance of these foreign objects getting impacted into the tooth is more when pulp chamber is open either because of traumatic injury or large carious exposure. A detailed case history, clinical, and radiographic examinations are required to ascertain the size, position, and likely composition of the object, and also the difficulty involved in its retrieval. This case report describes a self-introduced unusual foreign body and its retrieval from the root canal of upper central incisor by simple orthograde nonsurgical technique.